Impact of siRNA transfection on tumor development under experimental pathology of thyroid gland - Zaporozhan, V.M.; Maryniuk, G.S.; Kholodkova, O.L.; Bubnov, V.V.; Andronov, D.U. (Вiopolymers and Cell, 2013)
Aim. To assess the impact of siRNA transfection on the tumor development under experimental pathology of the thyroid gland. Methods. Experiments were performed on rats weighing 180 ± 20 g, which were divided into five groups: IA and IB – animals with simulated hypo- and hyperthyroid states and transplanted Guerin’s carcinoma; IIA and IIB – animals with simulated hypo- and hyperthyroid states and transplanted Guerin’s carcinoma in combination with siRNA transfection; III – control group with transplanted Guerin’s carcinoma in combination with siRNA transfection. Orthogonal dimensions of the tumor were measured. Histological and immunohistochemical researches of tumor samples were performed. Results. It has been shown that the inhibitory effect of short interfering RNA is realized to a greater extent in the hypothyroid state, indicating an important role of thyroid hormones in the regulation of expression of genes that control the cell cycle. We discuss a possible dependence of necrobiotic processes prevalence and characteristic changes in the blood vessels on the effects of thyroid hormones on angiogenesis and proliferative processes. Conclusions. siRNA trasfection leads to inhibition of tumor growth in animals with both hypo- and hyperthyroidism, but it is more pronounced at hypothyroidism.